Analysis of Consumer Satisfaction and Loyalty Factors with CRM Approach in Agribusiness E-commerce Company - Iqra Rizky Goranda; Popong Nurhayati; Megawati Simanjuntak (Journal of Consumer Sciences, 2021)
XYZ e-commerce is a company that sells an agricultural product that draws benefits from the COVID-19 pandemic. The purpose of this research was to analyze CRM factors, satisfaction, and consumer loyalty. This study using quantitative research selected with convenience sampling. The online survey applied toward 232 respondents who were unsatisfied with the service in Jabodetabek and processed using Structural Equation Model (SEM). Based on the SEM results, it was found that CRM has a significant effect on consumer satisfaction and consumer satisfaction with consumer loyalty. In contrast, CRM has no significant effect on consumer loyalty. This research concluded that XYZ needs to become a company that makes it easy for consumers, is professional, reliable and trustworthy. However, efforts need to be made to improve the relationship between criticism and suggestions, communication and providing information, regulating product availability, delivery time, and saving consumer costs—the results of this research results are expected to increase satisfaction and loyalty through the CRM approach.